Sosialisasi Anti Bullying dalam Meningkatkan Kesadaran dan Pencegahan Kasus Bullying di Sekolah - Khadafi Wijaya; Mustakimah Mustakimah (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
Golden Indonesia is the target and goal of the nation in the next few years, especially in 2045. In the formation of the Golden Indonesia, there is a need for character building in the next generation. Anti-bullying is one way that good character can be formed. Bullying is a behavior that can make people around feel pain or pain either verbally, physically, or mentally. This research uses a descriptive research method that displays the results of the analysis of the activities carried out. The implication of improving the nation's character and avoiding the character of bullying is the anti-bullying socialization with the theme “bullying is a wound not a joke